Information System Development for Pharmaceutics Production Line - Lakhoua Najeh; Fatma Khanchel (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
Information has now become the strategic weapon; its duration has become very short. So the system must be reliable and fast, which effectively justifies the importance of the computer tool, we have focused our work on its competitiveness and ensure its perfection in the concept of internal and external competition. The aim of this paper is to a project of an information system development of a production line in a pharmaceutical company after its passage from manual mode to automatic mode. In fact, system analysis technique is used in order to study the project of information system of the existing of the production line is presented.